2011
DOI: 10.1016/j.intell.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Are intelligence and creativity really so different?☆Fluid intelligence, executive processes, and strategy use in divergent thinking

Abstract: Contemporary creativity research views intelligence and creativity as essentially unrelated abilities, and many studies have found only modest correlations between them. The present research, based on improved approaches to creativity assessment and latent variable modeling, proposes that fluid and executive cognition is in fact central to creative thought. In Study 1, the substantial effect of fluid intelligence (Gf) on creativity was mediated by executive switching, the number of times people switched idea c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
439
5
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 530 publications
(512 citation statements)
references
References 40 publications
(60 reference statements)
39
439
5
16
Order By: Relevance
“…An extensive literature examines how these three domains relate. Openness to Experience is the most closely linked of the five factors to both intelligence (DeYoung, in press) and to creativity (Silvia, Nusbaum et al, 2009), and intelligence and creativity in turn relate at least modestly (Kim, 2005 andKim et al, 2010), although this remains controversial Silvia, 2011 andSilvia, 2008). Differentiating Openness to Experience into openness and intellect aspects might shed some light on this network of relationships.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive literature examines how these three domains relate. Openness to Experience is the most closely linked of the five factors to both intelligence (DeYoung, in press) and to creativity (Silvia, Nusbaum et al, 2009), and intelligence and creativity in turn relate at least modestly (Kim, 2005 andKim et al, 2010), although this remains controversial Silvia, 2011 andSilvia, 2008). Differentiating Openness to Experience into openness and intellect aspects might shed some light on this network of relationships.…”
Section: Resultsmentioning
confidence: 99%
“…People completed a wide range of tasks and questionnaires; the present analyses focus on the relations of creativity, intelligence, and personality, which have not been previously analyzed or reported (see Nusbaum & Silvia, 2011, Study 2).…”
Section: Methodsmentioning
confidence: 99%
“…Prior evidence has suggested that creative people or creative acts are associated with distinct types of attention. However, several variant relations between creativity and attention have been posited, such as creativity relating to the broad attentional scope (Ansburg & Hill, 2003), "leaky" attention, i.e., attention that allows "irrelevant" information to be noticed (Carson, Peterson, & Higgins, 2003;Mendelsohn & Griswold, 1964;Rawlings, 1985), broad conceptual scope (Rowe, Hirsh & Anderson, 2007), flexible attention (Vartanian, Martindale, & Kwiatkowski, 2007;Zabelina & Robinson, 2010), and executive cognition, which relies heavily on the ability to focus attention (Nusbaum & Silvia, 2011). These distinctions may arise because there are numerous forms, or measures, of creativity, such as successful performance on laboratory tests of divergent thinking, which assess the ability to find multiple solutions to a given problem within a limited amount of time, versus a measure of people's realworld creative achievements, assessed by a survey of people's creative achievements over their lifetime, as well as numerous forms of attention, with multiple components to each.…”
mentioning
confidence: 99%
“…Perhaps this is not surprising given that many of the creativity instruments were developed and standardized before the advent of modern psychometric analyses (Fishkin in creativity research, and although limited, their results are promising. These efforts addressed some critical issues in creativity measurement, such as evaluating reliability and validity (Chermahini, Hickendorff, & Hommel, 2012;Karwowski, 2014;Lee, Lee, & Youn, 2005;Primi, 2014;Silvia, 2011;Silvia et al, 2008;Wang, Ho, Cheng, & Cheng, 2014;Zampetakis, 2010), testing domain-specificity of creativity (Barbot, Tan, Randi, SantaDonato, & Grigorenko, 2012;Chen et al, 2006;Silvia, Kaufman, & Pretz, 2009), evaluating the rater's effect on performance assessment (Hung, Chen, & Chen, 2012) and modelling relationships between creativity and other constructs (Nusbaum & Silvia, 2011;Silvia, 2008). Expanding the use of these modern analyses could provide a better understanding of conflicting results in creativity research.…”
Section: Psychometric Propertiesmentioning
confidence: 99%